Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa pada Pembelajaran Matematika di Kelas VIII SMP Negeri 1 Bonepantai - Hasanudin Ibrahim; Majid Majid; Franky Alfrits Oroh (LP. Ma'arif Janggan Magetan, 2023)
This research is an experimental research which aims to find out whether there is an effect of the Problem Based Learning model on students' critical thinking skills in learning mathematics in class VIII SMP Negeri 1 Bonepantai. The hypothesis in this study is that there is an influence of the Problem Based Learning model on students' critical thinking skills in learning mathematics in class VIII SMP Negeri 1 Bonepantai. The population in this study were class VIII students of SMP Negeri 1 Bonepantai. Sampling was carried out using simple random sampling technique and it was obtained that class VIII'3 was the class taught using the Problem Based Learning model (experimental class) consisting of 23 students and class VIII'2 was the class taught using the Direct Learning model (class control) consisting of 24 students. The design used in the research in this study was the pretest-posttest control group design and the data collection technique was giving a test of critical thinking skills in the form of an essay. Inferential analysis in this study is the Anakova Test. The results of this study indicate that there is an influence of the Problem Based Learning model on students' critical thinking skills, where the mathematical critical thinking abilities of students who are taught with the Problem Based Learning model are higher than students who are taught with direct learning models on opportunity material in class VIII SMP Negeri 1 Bonepantai .